Hepatitis B Virus (HBV) Genotypes in an Ecuadorian Population: A Preliminary Study - Miguel Moncayo; Enrique Teran; Bernardo Gutierrez; Jorge Reyes; Johanna Cortez; Rodrigo Tobar; Gabriela Yerovi; Marcia Robalino; Ana Aguilar; Daniel Garzon-Chavez (Advances in Virology)
Chronic hepatitis B virus (HBV) infection affects 257–291 million people worldwide. The World Health Organization reported 890,000 HBV-related deaths in 2019, higher than reported previously. There are 10 HBV genotypes (A–J) subdivided into several subgenotypes that differ considerably by geography. Various virologic factors, including genotype and subgenotype, impact the odds of acquiring a chronic HBV infection, the type of treatment prescribed, and the risk of developing hepatocarcinoma. Information on the HBV genotypes and subgenotypes that circulate in Ecuador remains low. To address this gap, the current study took a preliminary look at HBV-infected human samples from this region to identify the most common genotypes and subgenotypes. Samples from 44 patients in the Andean, Coastal, and Amazon regions of Ecuador were amplified and two major genotypes were identified, genotype F (42/44; 95.5%) and genotype E (2 patients; 4.5%). The genotype F subgenotypes were F3 (35/42; 83.33%), F4 (6/42; 14.28%), and F1b (1/42, 2.39%). This is the first epidemiological study to assess the distribution of HBV genotypes in Ecuador. The findings can inform antiviral drug effectivity studies specific to HBV genotypes prevalent in South America.